Penser la pluralité des monnaies à partir de Polanyi : un essai de typologie - Blanc, Jérôme (ERES, 2014)
A large number of currencies has emerged for thirty years, far beyond the national currencies alone. It includes systems created by groups of citizens, others by territorial communities, and others by private companies for their own benefit. These currencies take various forms, ranging from electronic money on smart cards to settlement systems ...
Keywords: currencies; modern currencies

La société contre le marché - Skornicki, Arnault (The Life of Ideas, 2012)
A propos de : Karl Polanyi, La Subsistance de l'homme. La place de l'économie dans l'histoire et dans la société, Flammarion
Keywords: capitalisme; commerce; marché